2017
DOI: 10.1364/oe.25.012944
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent clusters in chloride photo-thermo-refractive glass by femtosecond laser bleaching of Ag nanoparticles

Abstract: We report photoluminescence in bulk chloride photo-thermo-refractive glass under irradiation with femtosecond laser pulses. The fluorescence originates from the bleaching of silver nanoparticles precipitating in the glass. Similarly to the conventional process of the femtosecond re-shaping of metal inclusions with diameter tens of nanometers, irradiation of the smaller nanoparticles results in a fast shrinking size with an ellipsoidal shape via photofragmentation. Under UV excitation, remaining sub-nanometer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, the particle species cannot move far from the origin due to limited space. Figure 2 shows that initially metallic nanoparticle is surrounded by NaAgCl shell with larger refractive index [9,11]. The femtosecond bleaching transforms AgNPs into closely spaced silver clusters, which can be bought back and restore the nanoparticle via thermal treatment within several minutes [11,16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the particle species cannot move far from the origin due to limited space. Figure 2 shows that initially metallic nanoparticle is surrounded by NaAgCl shell with larger refractive index [9,11]. The femtosecond bleaching transforms AgNPs into closely spaced silver clusters, which can be bought back and restore the nanoparticle via thermal treatment within several minutes [11,16].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently proposed, synthesized and characterized a novel PTR glass composition, which provides positive refractive index change [9,10]. X-ray diffraction analysis revealed the precipitation of the NaAgCl nanocrystalline phase which is responsible for the positive refractive index change with magnitude of as high as 8.7 × 10 −4 [9,11]. It has been shown that this glass open a way to fabricate the volume mix type Bragg gratings, which possess both refractive index and absorption coefficient modulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Royon et al [141] created silver clusters through a femtosecond laser shot inside a femtophotoluminescent glass, which can store information precisely. Klyukin et al [142] observed the presence of fluorescent clusters in chloride photothermorefractive glass under femtosecond laser irradiation. Birefringent [130] structures were obtained by means of multiple femtosecond laser pulses in nanoporous glass, where the minimum distance between dots was as small as 1.4 μm [143].…”
Section: Data Storage Materials and Devicesmentioning
confidence: 99%
“…The absorption of ultrashort pulse energy leads to local heating and the explosion of the metallic particle [31]. In Figure 9, process of AgNPs surrounded by NaCl-AgCl shell, destruction, is shown schematically [32]. The femtosecond bleaching transforms AgNPs into silver clusters.…”
Section: Bleaching Volume Bragg Gratings In Chloride Ptr Glassmentioning
confidence: 99%